A method for preparing a composite intermediate layer suitable for TLP connection of nickel-based alloys
The AuSi composite intermediate layer was prepared by powder metallurgy technology, and the atomization powdering, ball milling and cold isostatic press forming processes were used to solve the problems of poor consistency of the preparation process and large fluctuations in the quality of products in the prior art, and the uniform distribution of the welds and the preparation of high-strength joints were achieved.
Patent Information
- Application Number
- CN202411682001.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing AuSi composite intermediate layer preparation methods have problems with poor process consistency and large fluctuations in product quality, resulting in problems such as AuSi eutectic structure residues and solidification thermal cracks in the weld, which affects the strength and use temperature of the joint.
The AuSi composite intermediate layer is prepared by powder metallurgy technology. Through atomization powder making, ball milling and cold isostatic press forming processes, the addition amount and distribution uniformity of NiTi particles are accurately controlled, and process consistency and product quality are improved.
The consistency of the preparation process of the AuSi composite intermediate layer and the quality of the welded products are significantly improved, the problems of residual and solidification thermal cracks in the AuSi eutectic structure in the weld are solved, and the room temperature and high temperature strength of the joint are improved.
Smart Images

Figure CN119175373B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of diffusion welding, and in particular relates to a method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy. Background Art
[0002] Transient liquid phase diffusion bonding (TLP) technology has become a hot topic of research in recent years. This technology uses a material with a lower melting point than the parent material as an intermediate layer. When heated to the connection temperature, the intermediate layer melts and forms an instantaneous liquid film on the bonding surface. During the heat preservation process, the low-melting point components diffuse into the parent material or form high-melting point compounds, thereby increasing the remelting temperature of the weld. This allows low-temperature connection and high-temperature use of the joint, reducing the damage to the parent material performance caused by the welding heat process. At present, the technical characteristics of transient liquid phase bonding technology are different due to different connection temperatures.
[0003] When the melting temperature of the intermediate layer used is below 450℃, which is often referred to as the soldering temperature, the increase in the remelting temperature of the weld mainly depends on the high melting point compounds formed by the reaction of the intermediate layer. This part of the intermediate layer is mainly composed of copper-tin, silver-indium and other solders. This is because during the welding process, the intermediate layer materials (such as copper-tin, silver-indium, etc.) will react with the metals being welded to form new intermetallic compounds. The melting points of these compounds are often higher than the melting points of the original solder. From the binary phase diagram, it can be seen that the eutectic point temperatures of copper and tin, silver and indium are very low, which greatly reduces the welding temperature. However, as the insulation time after welding increases, these elements will further react to form more complex intermetallic compounds. The melting points of the copper-tin, silver-indium and other compounds formed can be much higher than the melting point of the original solder, and the melting point can reach more than 650℃. This is because the structure of the intermetallic compound is more complex and requires higher energy to melt. Therefore, although the initial welding temperature is low, the remelting temperature of the weld is increased due to the high melting point compounds formed by the reaction of the intermediate layer. This can eliminate the eutectic liquid phase in the weld and form a weld structure dominated by solid solution and intermetallic compounds. However, most of the intermetallic compounds formed by this method are continuously distributed, and their hard and brittle characteristics lead to generally low joint strength.
[0004] When the melting temperature of the intermediate layer is above 450℃, which is often called the brazing temperature, the increase in the remelting temperature of the weld mainly depends on the diffusion of the melting elements into the base material. This part of the intermediate layer is mainly composed of solders containing Si and B elements such as BNi2. Si and B have small atomic radii and are easy to diffuse into the base material to form a solid solution, but the joint needs to be subjected to long-term high-temperature heat treatment after welding to make the element diffusion uniform, so as to ensure its reliable high-temperature strength, which reduces production efficiency and increases the risk of deterioration of base material performance.
[0005] In view of this, we designed a method for preparing a composite intermediate layer by screen printing NiTi particles on the surface of AuSi eutectic metal foil (patent number: ZL202111282454.9), based on the Au-Si low-melting-point eutectic binary phase diagram and the principle that Si can form a high-melting-point NiSiTi ternary compound with Ni and Ti at low temperatures. This intermediate layer was used to successfully connect nickel-titanium alloy and sapphire. This method can transform the AuSi eutectic structure in the weld into a dispersion-strengthened structure dominated by pure Au (melting point 1064°C) and NiSiTi whiskers (calculated melting point 1647°C), while the welding temperature is only 430°C. This method can not only improve the mechanical properties of the joint, but also avoid damage to the parent material properties during the thermal process.
[0006] However, in actual application, it was found that this method also has many problems. First, the uniformity and thickness of the NiTi particles screen-printed on the AuSi foil are greatly affected by the operator's operating level; second, the NiTi particles and pine oil alcohol are easily separated from each other after long-term use, and the NiTi particles are more likely to agglomerate due to surface energy. This leads to a lack of NiTi particles in some parts of the weld, resulting in a large amount of AuSi eutectic structure in these parts after welding, while the presence of excessive NiTi particles in other parts causes the intermediate layer to solidify and shrink earlier, resulting in thermal cracks near the NiTi particles (see attached). Figure 1 ); When the assembled AuSi interlayer is placed for a long time, the pine oil used as a binder is easy to volatilize, which will cause NiTi particles to fall off during the transportation and furnace loading process of the AuSi interlayer. These problems will cause some TLP welded joints to not only fail to reach the predetermined operating temperature, but also have low room temperature strength. Summary of the invention
[0007] In view of the above-mentioned shortcomings, the present invention provides a method for preparing a composite intermediate layer suitable for TLP connection of nickel-based alloys. The present invention adopts a powder metallurgy process to prepare the AuSi composite intermediate layer, and through chemical calculation of mass ratio, accurately controls the addition amount of NiTi particles, improves the uniformity of the distribution of NiTi particles in the AuSi matrix, and solves the problems of poor process consistency and large fluctuations in the quality of the welded product in the AuSi composite intermediate layer prepared by the screen printing process.
[0008] The present invention provides a method for preparing a composite intermediate layer, and the key points of the technical solution include an atomization powder making process, a ball milling process and a cold isostatic pressing process; AuSi powder is prepared by the atomization powder making process, and then the AuSi powder is mixed with NiTi powder by the ball milling process, and finally the composite intermediate layer blank is obtained by cold isostatic pressing.
[0009] Atomization powder making process: Pure Au and pure Si are mixed in a mass ratio of 96.85:3.15 and placed in an atomization powder making device. A high-frequency power supply is used to heat the mixture to between 1560°C and 1570°C. The argon atomization pressure is 1MPa-1.5MPa, and the nozzle diameter of the equipment is 3mm. After atomization cooling, the collected AuSi powder is sieved, and AuSi powder with a particle size of ≤30μm is selected for the preparation of the composite intermediate layer.
[0010] Ball milling process: AuSi powder particle size ≤30μm, NiTi powder particle size ≤15μm, the mass ratio of AuSi powder to NiTi powder is between 7.5:1 and 8:1, a planetary ball mill is used, the ball milling atmosphere is high-purity argon, the ball material is ZrO2, the ball material ratio is between 2:1 and 3:1, the ball milling time is 3h, and the rotation speed is constant at 200r / min.
[0011] Cold isostatic pressing process: The pre-forming process pressure parameters are 25MPa-35MPa and the holding time is ≥120s. The cold isostatic pressing parameters are pressure ≥250MPa and the holding time is ≥180s.
[0012] The composite intermediate layer blank obtained by cold isostatic pressing is rolled into a 100μm thick metal foil by a multi-stage cold rolling process; the surface of the rolled intermediate layer foil is polished and cleaned, and then used for NiTi alloy homogeneous TLP diffusion welding connection, and the welding process includes: assembling the sample to be welded, clamping the fixture, putting it into a vacuum diffusion welding furnace, applying pressure, evacuating the vacuum, heating from room temperature to 430℃ at a rate of 10℃ / min, keeping the temperature for 30min, then cooling to 200℃ at a rate of 10℃ / min, and then cooling the furnace to room temperature and taking it out of the furnace; after shear test, the average shear strength of the welded joint at room temperature reaches 147MPa, and the average shear strength at 700℃ reaches 47MPa.
[0013] Beneficial effects of the technical solution of the present invention:
[0014] 1. The technical solution of the present invention prepares the AuSi composite intermediate layer through a powder metallurgy process, improves the uniformity of the distribution of NiTi particles in the AuSi matrix, and solves the problems of residual AuSi eutectic structure in the weld and solidification hot cracks in the weld caused by the uneven distribution of NiTi particles. This process improves the consistency of the preparation process of the AuSi composite intermediate layer and can significantly improve the quality of the welded product.
[0015] 2. The technical solution of the present invention accurately calculates the mass ratio of AuSi powder and NiTi powder that can make the AuSi powder react completely through the chemical reaction formula, and accurately controls the amount of NiTi particles added through the mechanical ball milling process, thereby solving the problem that excessive Ti elements easily react with Au elements to form brittle Au4Ti compounds during welding.
[0016] 3. The technical solution of the present invention can realize the mass production and long-term storage of AuSi composite intermediate layers, and is convenient for realizing large-gap TLP diffusion welding and crack repair welding. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Solidification hot cracks caused by excessive NiTi particles;
[0018] Figure 2 The morphology of AuSi particles after atomization and screening;
[0019] Figure 3 The structure formed by NiTi particles with a particle size of 50 μm;
[0020] Figure 4 The structure formed by NiTi particles with a particle size of 25 μm;
[0021] Figure 5 The structure formed by NiTi particles with a particle size of 15μm. DETAILED DESCRIPTION
[0022] The implementation method takes the AuSi composite intermediate layer prepared by the technical solution of the present invention connecting NiTi alloy as an example.
[0023] A method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy comprises an atomization powder making process, a ball milling process and a cold isostatic pressing process.
[0024] Atomization powder making process: Pure Au and pure Si are mixed in a mass ratio of 96.85:3.15 and placed in an atomization powder making device. A high-frequency power supply is used to heat the mixture to between 1560°C and 1570°C. The argon atomization pressure is 1MPa-1.5MPa, and the nozzle diameter of the equipment is 3mm. After atomization cooling, the collected AuSi powder is sieved, and AuSi powder with a particle size of ≤30μm is selected for the preparation of the composite intermediate layer.
[0025] The basis for the formulation of the atomization powder making process is as follows: First, determine the ratio of Au and Si, and form a gold-silicon eutectic alloy according to the mass ratio of 96.85:3.15; secondly, determine the screening standard for AuSi powder. After testing AuSi powders of different particle sizes, it was found that AuSi powders with a particle size of >30μm have the following disadvantages in the preparation process of the composite intermediate layer:
[0026] 1. The larger the AuSi powder particle size, the higher the probability of hollow inside;
[0027] 2. The larger the AuSi powder particle size, the worse the uniformity of NiTi particle distribution after mixing with NiTi particles;
[0028] 3. The larger the AuSi powder particle size, the higher the porosity of the composite intermediate layer blank obtained by cold isostatic pressing.
[0029] Therefore, the AuSi powder screening standard is particle size ≤ 30 μm (see Appendix Figure 2 ).
[0030] Then the AuSi melting temperature is determined. It is verified by experiments that when the heating temperature is less than 1560℃, the melt fluidity decreases and the molten liquid flow is broken worse under the action of high-speed airflow. When the heating temperature is greater than 1570℃, the probability of the hard and brittle amorphous phase appearing after the melt is rapidly cooled after atomization increases, which is not conducive to subsequent cold isostatic pressing.
[0031] Finally, the argon atomization pressure is determined. When the argon atomization pressure is less than 1MPa, the proportion of AuSi powder with a particle size of ≤30μm is small. When the argon atomization pressure is greater than 1.5MPa, although the proportion of AuSi powder with a particle size of ≤30μm increases, the proportion of hollow powder produced will also increase accordingly. After welding, pore defects are easily formed in the weld, reducing the durability and fatigue strength of the joint. Therefore, it is more appropriate to select the argon atomization pressure between 1MPa-1.5MPa.
[0032] Ball milling process: AuSi powder particle size ≤30μm, NiTi powder particle size ≤15μm, the mass ratio of AuSi powder to NiTi powder is between 7.5:1 and 8:1, a planetary ball mill is used, the ball milling atmosphere is high-purity argon, the ball material is ZrO2, the ball material ratio is between 2:1 and 3:1, the ball milling time is 3h, and the rotation speed is constant at 200r / min.
[0033] Ball milling process formulation basis: According to the chemical reaction formula calculation, when the mass ratio of AuSi powder to NiTi particles is 8.32:1, it can ensure that Si element reacts completely with Ni and Ti elements and forms NiSiTi ternary whiskers, but this is only a theoretical calculation result. It has been found through experiments that for NiTi particles with a particle size of more than 40μm, after dense NiSiTi whiskers are formed on the surface, they will hinder the further reaction of Ni and Ti elements in the particles with Si in the middle layer (see Appendix Figure 3 Therefore, even if the welding temperature is 430°C and the temperature is kept for a long time, NiTi particles and AuSi eutectic will still remain in the weld.
[0034] The experiment found that when the NiTi particle size is ≤25μm, the specific surface energy increases, which will accelerate the reaction rate of Ni, Ti and Si elements. The NiTi particles can be completely consumed by heating at 430℃ for 30min (see Appendix). Figure 4 However, the NiSiTi whiskers formed by particles of this size are densely distributed in clusters, with poor dispersion, and poor dispersion strengthening effect on the weld. When the NiTi particle size is ≤15μm, the NiSiTi whiskers formed under the condition of 430℃ insulation for 30min are relatively dispersed (see Appendix Figure 5 ), which has a good effect on the dispersion strengthening of the weld. According to experimental verification, when the NiTi particle size is ≤15μm and the mass ratio of AuSi powder to NiTi particles is between 7.5:1-8:1, the weld microstructure after brazing thermal cycle is optimal. A ratio higher than this value will result in residual eutectic structure in the weld, and a ratio lower than this value will result in more weld structure defects.
[0035] Cold isostatic pressing process: The pre-forming process pressure parameters are 25MPa-35MPa and the holding time is ≥120s. The cold isostatic pressing parameters are pressure ≥250MPa and the holding time is ≥180s.
[0036] The basis for the cold isostatic pressing process is as follows: First, the preforming process parameters are determined. Through experiments, different loading pressures such as 5MPa, 10MPa, 20MPa, 30MPa, and 40MPa and holding times such as 0.5min, 1min, and 2min are tried. It is found that when the pressure is less than 20MPa, the preformed sheet is loose and fragile. When the pressure reaches 40MPa and the holding time is too short, it is easy to delaminate and crack. Therefore, the optimal preforming process pressure parameters are determined to be 25MPa-35MPa and the holding time is ≥120s. The prepared preformed sheets are bagged and wait for subsequent operations. In order to further improve the density of the braze-coated sheet, the preformed sheet obtained after static pressing at room temperature is subjected to cold isostatic pressing. Since AuSi powder has good plasticity and NiTi particles that are difficult to deform have small particle size and low content, when the cold isostatic pressing pressure is ≥250MPa and the holding time is ≥180s, the porosity of the composite interlayer can be reduced to 1.25%. If the pressure is further increased or the holding time is extended, the trend of the composite interlayer porosity continuing to decrease is no longer obvious.
[0037] The composite intermediate layer blank obtained by cold isostatic pressing is rolled into a 100μm thick metal foil by a multi-stage cold rolling process; the surface of the rolled intermediate layer foil is polished and cleaned, and then used for NiTi alloy homogeneous TLP diffusion welding connection. The welding process includes: assembling the sample to be welded, clamping the fixture, placing it in a vacuum diffusion welding furnace, applying pressure, evacuating the vacuum degree, heating from room temperature to 430℃ at a rate of 10℃ / min, keeping the temperature for 30min, then cooling to 200℃ at a rate of 10℃ / min, and then cooling the furnace to room temperature and taking it out of the furnace. According to the shear test, the average shear strength of the welded joint at room temperature can reach 147MPa, and the average shear strength at 700℃ can reach 47MPa.
[0038] Example 1
[0039] (1) Pure Au and pure Si are mixed in a mass ratio of 96.85:3.15 and placed in an atomizing powder making device. The mixture is heated to 1560°C using a high-frequency power supply. The molten alloy flows out of the nozzle in a bottom pouring manner and is broken up by high-pressure argon gas at the nozzle. The argon gas atomization pressure is 1 MPa and the nozzle diameter of the equipment is 3 mm. After atomization cooling, the collected AuSi powder is sieved, and the AuSi powder with a particle size of ≤30 μm is screened for preparing the composite intermediate layer.
[0040] (2) AuSi powder with a particle size of ≤30 μm and NiTi powder with a particle size of ≤15 μm were placed in a planetary ball mill at a mass ratio of 7.5:1, wherein the ball material was ZrO2 ceramic, the ball-to-material ratio was 2:1, the ball milling atmosphere was high-purity argon, the ball milling time was 3 h, and the rotation speed was constant at 200 r / min;
[0041] (3) Add the ball-milled mixed powder into the mold, and use a tablet press to perform pre-forming at room temperature to obtain a pre-formed sheet. The pre-forming process pressure parameters are 25 MPa and holding time 120 s. Put the pre-formed sheet into a rubber sleeve and put it into a cold isostatic press for oil pressure to obtain a composite intermediate layer body. The cold isostatic pressing parameters are pressure 250 MPa and holding time 180 s.
[0042] (4) rolling the composite intermediate layer blank obtained by cold isostatic pressing into a metal foil with a thickness of 100 μm by a multi-stage cold rolling process;
[0043] (5) The surface of the rolled intermediate layer foil was polished with 1500# sandpaper and ultrasonically cleaned with acetone before being used for homogeneous TLP diffusion welding of NiTi alloy. The welding process was as follows: the sample to be welded was assembled, clamped with a graphite fixture, placed in a vacuum diffusion welding furnace, and a pressure of 1 MPa was applied. When the vacuum degree reached 5×10 -4 Pa, heating from room temperature to 430℃ at a rate of 10℃ / min, keeping the temperature for 30min, then cooling to 200℃ at a rate of 10℃ / min, then cooling to room temperature and taking out of the furnace;
[0044] (6) After shear testing, the average shear strength of the welded joint at room temperature can reach 145 MPa, and the average shear strength at 700°C can reach 39 MPa.
[0045] Example 2
[0046] (1) Pure Au and pure Si were mixed in a mass ratio of 96.85:3.15 and placed in an atomizing powder making device. The mixture was heated to 1570°C using a high-frequency power supply. The molten alloy liquid flowed out of the nozzle in a bottom pouring manner and was broken up by high-pressure argon gas at the nozzle. The argon gas atomization pressure was 1.5 MPa and the nozzle diameter of the equipment was 3 mm. After atomization cooling, the collected AuSi powder was sieved, and the AuSi powder with a particle size of ≤30 μm was screened for preparing the composite intermediate layer.
[0047] (2) AuSi powder with a particle size of ≤30 μm and NiTi powder with a particle size of ≤15 μm were placed in a planetary ball mill at a mass ratio of 8:1, wherein the ball material was ZrO2 ceramic, the ball-to-material ratio was 3:1, the ball milling atmosphere was high-purity argon, the ball milling time was 3 h, and the rotation speed was constant at 200 r / min;
[0048] (3) Add the ball-milled mixed powder into the mold, and use a tablet press to perform pre-forming at room temperature to obtain a pre-formed sheet. The pre-forming process pressure parameters are 35 MPa and the holding time is 130 s. Put the pre-formed sheet into a rubber sleeve and put it into a cold isostatic press for oil pressure to obtain a composite intermediate layer body. The cold isostatic pressing parameters are pressure 250 MPa and holding time 180 s.
[0049] (4) rolling the composite intermediate layer blank obtained by cold isostatic pressing into a metal foil with a thickness of 100 μm by a multi-stage cold rolling process;
[0050] (5) The surface of the rolled intermediate layer foil was polished with 1500# sandpaper and ultrasonically cleaned with acetone before being used for homogeneous TLP diffusion welding of NiTi alloy. The welding process was as follows: the sample to be welded was assembled, clamped with a graphite fixture, placed in a vacuum diffusion welding furnace, and a pressure of 1 MPa was applied. When the vacuum degree reached 5×10 -4 Pa, heating from room temperature to 430℃ at a rate of 10℃ / min, keeping the temperature for 30min, then cooling to 200℃ at a rate of 10℃ / min, then cooling to room temperature and taking out of the furnace;
[0051] (6) After shear testing, the average shear strength of the welded joint at room temperature can reach 142 MPa, and the average shear strength at 700°C can reach 41 MPa.
[0052] Example 3
[0053] (1) Pure Au and pure Si were mixed in a mass ratio of 96.85:3.15 and placed in an atomizing powder making device. The mixture was heated to 1565°C using a high-frequency power supply. The molten alloy liquid flowed out of the nozzle in a bottom pouring manner and was broken up by high-pressure argon gas at the nozzle. The argon gas atomization pressure was 1.2 MPa and the nozzle diameter of the equipment was 3 mm. After atomization cooling, the collected AuSi powder was sieved and the AuSi powder with a particle size of ≤30 μm was screened for preparing the composite intermediate layer.
[0054] (2) AuSi powder with a particle size of ≤30 μm and NiTi powder with a particle size of ≤15 μm were placed in a planetary ball mill at a mass ratio of 7.7:1, wherein the ball material was ZrO2 ceramic, the ball-to-material ratio was 2:1, the ball milling atmosphere was high-purity argon, the ball milling time was 3 h, and the rotation speed was constant at 200 r / min;
[0055] (3) Add the ball-milled mixed powder into the mold, and use a tablet press to perform pre-forming at room temperature to obtain a pre-formed sheet. The pre-forming process pressure parameters are 30 MPa and holding time 125 s. Put the pre-formed sheet into a rubber sleeve and put it into a cold isostatic press for oil pressure to obtain a composite intermediate layer body. The cold isostatic pressing parameters are pressure 255 MPa and holding time 190 s.
[0056] (4) rolling the composite intermediate layer blank obtained by cold isostatic pressing into a metal foil with a thickness of 100 μm by a multi-stage cold rolling process;
[0057] (5) The surface of the rolled intermediate layer foil was polished with 1500# sandpaper and ultrasonically cleaned with acetone before being used for homogeneous TLP diffusion welding of NiTi alloy. The welding process was as follows: the sample to be welded was assembled, clamped with a graphite fixture, placed in a vacuum diffusion welding furnace, and a pressure of 1 MPa was applied. When the vacuum degree reached 5×10 -4 Pa, heating from room temperature to 430℃ at a rate of 10℃ / min, keeping the temperature for 30min, then cooling to 200℃ at a rate of 10℃ / min, then cooling to room temperature and taking out of the furnace;
[0058] (6) After shear testing, the average shear strength of the welded joint at room temperature can reach 147MPa, and the average shear strength at 700℃ can reach 47MPa.
Claims
1. A method for preparing a composite intermediate layer suitable for nickel-based alloy TLP connection, characterized in that: The method comprises an atomization powder making process, a ball milling process and a cold isostatic pressing process; AuSi powder is prepared by the atomization powder making process, and then the AuSi powder and NiTi powder are mixed at a mass ratio of 7.5:1-8:1 by the ball milling process, the ball milling process is carried out by a planetary ball mill, the AuSi powder particle size is ≤30μm, the NiTi powder particle size is ≤15μm, and finally a composite intermediate layer blank is obtained by cold isostatic pressing.
2. The method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy according to claim 1, characterized in that: AuSi powder was prepared, and the mass ratio of pure Au to pure Si in the raw material was 96.85:3.
15.
3. The method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy according to claim 1, characterized in that: Atomization powder making process: Pure Au and pure Si are mixed according to the mass ratio and placed in the atomization powder making device, heated to between 1560℃-1570℃ by a high-frequency power supply, the argon atomization pressure is 1MPa-1.5MPa, and the AuSi powder is collected after atomization cooling.
4. The method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy according to claim 3, characterized in that: Atomization powder making process: The nozzle diameter of the equipment is 3mm. After atomization cooling, the collected AuSi powder is sieved to select AuSi powder with a particle size of ≤30μm.
5. The method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy according to claim 1, characterized in that: Ball milling process: The ball milling atmosphere is high-purity argon, the ball material is ZrO2, the ball-to-material ratio is between 2:1-3:1, the ball milling time is 3h, and the rotation speed is constant at 200r / min.
6. The method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy according to claim 1, characterized in that: Cold isostatic pressing process: The pre-forming process pressure parameters are 25MPa-35MPa and the holding time is ≥120s. The cold isostatic pressing parameters are pressure ≥250MPa and the holding time is ≥180s.
7. The method for preparing a composite intermediate layer suitable for TLP connection of a nickel-based alloy according to claim 6, characterized in that: The composite intermediate layer blank obtained by cold isostatic pressing is rolled into a 100 μm thick metal foil by a multi-stage cold rolling process; After the rolled intermediate layer foil surface is polished and cleaned, it is used for NiTi alloy homogeneous TLP diffusion welding connection, and the welding process includes: assembling the sample to be welded, clamping the fixture, placing it in a vacuum diffusion welding furnace, applying pressure, evacuating the vacuum degree, heating from room temperature to 430°C at a rate of 10°C / min, keeping the temperature for 30 minutes, then cooling to 200°C at a rate of 10°C / min, and then cooling the furnace to room temperature and taking it out of the furnace; After shear testing, the average shear strength of the welded joint at room temperature reached 147MPa, and the average shear strength at 700℃ reached 47MPa.
Citation Information
Patent Citations
A method for low-temperature sealing of sapphire optical windows and a sealing joint
CN113857606B
Cast high-temperature alloy and martensitic stainless steel diffusion welding method
CN110666328A
Sapphire light window low-temperature sealing-in method and sapphire light window low-temperature sealing-in joint
CN113857606A